FAKTOR-FAKTOR PENENTU IMPLEMENTASI E-GOVERNMENT PEMERINTAH DAERAH DI INDONESIA - Sipahutar, Indra Sarjono; sutaryo, sutaryo (Program Studi Akuntansi FPEB UPI, 2017)
Abstract. This study aims to examine the effect of region own source revenue (PAD), capital expenditure, internal auditor capability, internal auditor expertise to the implementation of e-government on municipalities in Indonesia. This study used a dependent variable like index ranking of e-government local government (PeGI) and so the independent variable used is region own source revenue, capital expenditure, internal auditor capability, internal auditor expertise. The sampling technique in this study is purposive sampling. The criteria are determined based on the index ranking of e-government local government (PeGI) issued by the Kemenkominfo. The criteria are divided into five dimensions, namely policies, institutions, infrastructure, applications, and planning. Based on the criteria that have been established, there are 198 municipalities as a sample. Data in this study is collected from the Local Government Financial Report (LKPD) in 2012-2014 and the index ranking of e-government implementation (PeGI) in 2012-2014. Data were analyzed using descriptive statistics, classical assumption test and multiple linear regression. The results showed that political region own source revenue (PAD), capital expenditure, internal auditor capability have an effect on e-government implementation. However, internal auditor expertise does not have an effect on e-government implementation in Indonesia.Keywords: e-government; region own source revenue; capital expenditure; capabilityAbstrak. Penelitian ini bertujuan untuk menguji pengaruh pendapatan sumber pendapatan daerah (PAD), belanja modal, kemampuan auditor internal, keahlian auditor internal terhadap pelaksanaan e-government di kota-kota di Indonesia. Penelitian ini menggunakan variabel dependen seperti indeks ranking pemerintah daerah e-government (PeGI) dan variabel independen yang digunakan adalah pendapatan sumber sendiri, pengeluaran modal, kemampuan auditor internal, keahlian auditor internal. Teknik pengambilan sampel dalam penelitian ini adalah purposive sampling. Kriteria tersebut ditentukan berdasarkan peringkat indeks pemerintah daerah e-government (PeGI) yang dikeluarkan oleh Kemenkominfo. Kriteria dibagi menjadi lima dimensi, yaitu kebijakan, institusi, infrastruktur, aplikasi, dan perencanaan. Berdasarkan kriteria yang telah ditetapkan, terdapat 198 kotamadya sebagai sampel. Data dalam penelitian ini dikumpulkan dari Laporan Keuangan Pemerintah Daerah (LKPD) 2012-2014 dan peringkat indeks implementasi e-government (PeGI) pada tahun 2012-2014. Data dianalisis dengan menggunakan statistik deskriptif, uji asumsi klasik dan regresi linier berganda. Hasil penelitian menunjukkan bahwa sumber pendapatan daerah politik (PAD), belanja modal, kemampuan auditor internal berpengaruh terhadap implementasi e-government. Namun, keahlian auditor internal tidak berpengaruh pada implementasi e-government di Indonesia.Kata Kunci: e-government; sumber pendapatan daerah; belanja modal; kapabilitas